Control of bidirectional quadratic DC-DC converters for storage support of DC power grids - Fernao Pires, Vitor (2018)
Many applications require a DC bus supporting connections to several renewable energy sources, storage systems and loads. However, due to the intermittent nature of renewable energy sources and load variations it is essential to stabilize the voltage of the DC bus. Usually a battery is used to support the DC bus voltage, but their continuous charge and discharge cycling will affect his lifetime. Thus, the use of a storage system based in supercapacitors provides an interesting alternative to stabilize the DC power grid. In this context, this work presents a study of a storage system based in supercapacitors combined with a bidirectional quadratic DC-DC converter to support the DC bus. A full design of the controllers for the quadratic converter is also presented. The behaviour of the system will be tested through several simulation results.